What do we know about the punctuated equilibrium theory in China? A systematic review and research priorities. - van den Dool, Annemieke; Li, Jialin (Policy Studies Journal, 2023)
The punctuated equilibrium theory (PET) shows that government policy is mostly stable with occasional drastic change, which scholars attribute to institutional friction and limited information processing capacity. Although the existing PET literature predominantly focuses on democracies, scholars have started to apply the theory to authoritarian countries. Autocracies are a fertile testing ground for the theory's underlying mechanisms because they appear to experience less institutional friction but more informational restrictions than democracies. However, PET studies on autocracies are still rare. To deepen our understanding of the PET and the policy process beyond democracies, we conduct a systematic review of 88 Chinese language PET journal articles. We show that Chinese language PET research is increasing. Contrary to the English language PET literature, most Chinese studies are qualitative, while a key similarity is the weak operationalization of PET core concepts. The reviewed studies confirm a punctuated equilibrium pattern of policymaking in China but provide only limited evidence for more intense punctuations compared with democracies. Future PET research on China ought to use long‐term data sets and examine institutional friction and information processing by policymakers. We also argue for more international exchange and comparative research to advance our understanding of the policy process in China and other autocracies.